Chiral Auxiliaries and Chirogenesis II - Borovkov, Victor (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Reprint Book highlights and overviews the most important and novel aspects of chiral auxiliary and chirogenesis in different natural/physical sciences and in modern technologies. In particular, some newly emerging classes of molecules used for these purposes have been described. Furthermore, some important experimental and theoretical issues associated with the chirality field have been addressed. This book consists of one review article and six research papers and is of interest for general chemistry readership, including graduate and post-graduate students, and for researchers specializing in the fields of chirality and stereochemistry